2021
DOI: 10.3390/su132011441
|View full text |Cite
|
Sign up to set email alerts
|

The Convergence Model of Education for Sustainability in the Transition to Digital Economy

Abstract: The paper studies the problem of updating educational programs and content, taking into account changing requirements of standards and employers for qualifications and competencies of specialists. First, we show that the updating process in transition to digital economy is associated with the transition to the convergence model of education providing its sustainability perspective. Furthermore, we propose the technique and develop basic models and methods for updating based on the convergence approach, for ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Thus, PERVAINCONSA is a scale that provides reliable scores and valid interpretations of the behavior of a young consumer of an online store [12,84]. Since for these consumers, online shopping is not a simple activity oriented to obtain a specific product or service, what they value is browsing from one page to another, viewing products, and placing them in a shopping cart, even virtual shopping can be a form of entertainment for this type of online consumers [85,86], which makes it relevant to know and constantly evaluate their perception about the products of an online store.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PERVAINCONSA is a scale that provides reliable scores and valid interpretations of the behavior of a young consumer of an online store [12,84]. Since for these consumers, online shopping is not a simple activity oriented to obtain a specific product or service, what they value is browsing from one page to another, viewing products, and placing them in a shopping cart, even virtual shopping can be a form of entertainment for this type of online consumers [85,86], which makes it relevant to know and constantly evaluate their perception about the products of an online store.…”
Section: Discussionmentioning
confidence: 99%
“…In a rapidly evolving global society, convergence education equips students with the versatility and adaptability needed to thrive in various professional domains. It bridges the gap between different areas of knowledge and promotes lifelong and sustainable learning [54].…”
Section: Silk Road and Convergence Educationmentioning
confidence: 99%
“…In another study, the authors proposed a technique and developed basic models and methods for updating based on the convergent approach. They assessed the degree of convergence of competence models and educational content and showed that the updating process in the transition to the digital economy is associated with the convergence model of education, which provides sustainability (Deev et al., 2021). The present study aims to map and visualise current perspectives on the topic of active learning by analysing and interpreting the different elements that make up education ecosystems within the European Higher Education Area (Rodríguez‐Sabiote et al., 2020).…”
Section: Review Of Recent Research and Publicationsmentioning
confidence: 99%